KONFLIK PSIKOLOGIS PERCINTAAN DALAM PEMENTASAN OPERA MELAYU BULANG CAHAYA KARYA FEDLI AZIS - Mulfransware Yusda; Syafrial '; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research-based psychology literature. Issues discussed were conflict, the causes and effects of psychological conflict in staging opera romance wither Bulang Cahaya works Fedli Aziz. This study uses qualitative descriptive method with data reduction techniques, data presentation and conclusion. The data collection was done by using the recording and documentation of data relating to the causes, effects, and psychological conflict in staging opera romance wither Bulang Cahaya works Fedli Aziz. The data is then analyzed through data analysis techniques. The results showed that the romance of psychological conflicts that occur in the main character, namely Tengku Buntat and Raja Djaffar is a disorder that comes from a variety of opposing desires within the individual and the group. The main cause of the rise of romance inner psychological conflicts motivated by the main character figures, both from the individual himself or another character.As a result of prolonged psychological conflicts romance experienced by the main character resulting emotional impact.Keywords: psychological conflict, characters, performances